Firmness of the basic movements of system – the rotor with the fixed point, the case and the autobalancer - Філімоніхін, Геннадій Борисович; Гончаров, Валерій Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Is explored the stability of the main motions and flowline of transitional processes of the system witch consist of rotorwith a fixed point, corps and autobalancer